Trilha de aprendizagem – a termorregulação corporal para a alfabetização científica - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
The teaching of science, especially chemistry, often faces the challenge of making abstract and complex concepts accessible and relevant to students. Thermochemistry, for example, requires a great deal of abstraction, which can discourage many students. In this context, the present research seeks to innovate by proposing a pedagogical approach that connects the principles of thermochemistry to the biological processes of the human body, using food as a starting point. The research used a qualitative and quantitative approach to assess the impact of a learning path. This research was conducted at a state school in the state of Amapá in the city of Macapá, with 30 students enrolled in the 1st year of high school. The results show that there were significant changes in the students' narratives regarding the proposed theme, with a slight increase in basic Scientific Literacy (SL) indicators compared to the initial results, where more than 80% of students were able to define the basic concepts of thermochemistry. The implementation of the Learning Trail on Body Thermoregulation proved to be an effective strategy for promoting scientific literacy in chemistry education, especially in the context of thermochemistry, by connecting abstract concepts to everyday phenomena.
Keywords: Avaliação da aprendizagem; Avaliação da aprendizagem; Termorregulação corporal; Alimentação e Energia; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA; ODS 3 – Saúde e bem-estar; ODS 4 – Educação de qualidade